Hamstring, Bone-patellar Tendon-bone, Quadriceps, and Peroneus Longus Tendon Autografts for Primary Isolated Anterior Cruciate Ligament Reconstruction: A Systematic Review - Dhaval H. Sagala (Journal of Orthopedics, Traumatology and Rehabilitation)
Background: Anterior cruciate ligament reconstruction (ACLR) involves surgically restoring the injured ACL through the placement of graft material. The selection of graft material plays a crucial role in ensuring optimal knee stability postsurgery. Using autografts of the hamstring, bone-patellar tendon-bone (BPTP), quadriceps, and peroneus longus tendon (PLT), the current systematic study aimed to assess the clinical and functional results of patients undergoing ACLR. Methods: Literature search exploration was conducted using databases such as PubMed, Medline, Web of Science, and Cochrane Library, supplemented by additional resources such as Google Scholar and clinical trials.gov, spanning from 2014 to 2024. The two-part tool was employed to analyze five distinct domains. For evaluation of the quality of diagnostic accuracy studies, a quality assessment tool was implemented. Results: Seventeen studies were incorporated. Most studies indicated considerable enhancements in clinical function, postsurgical knee stability, and osteoarthritis alterations. Nonetheless, these autografts present a reduced risk of certain complications including anterior knee pain, discomfort during kneeling, and extension loss. The assessment of risks in the study revealed that 50% were categorized as having a low risk, whereas 32% had an unclear risk and 18% of cases were classified as not applicable. Conclusion: The present systematic review highlights the survival rates and joint stability across various graft options including BPTP, hamstring, quadricep, and especially PLT. These autografts are safe, reliable, and versatile choices deserving of attention in forthcoming ACL reconstruction investigations.